BBC Coverage of the Aggression on Gaza 2021: Critical Discourse Analysis of Arabic and English Versions - Yousef Y. Abu Hashish; Ahmed A. Ismail; Husam A. Abusaada (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to analyse the trends in the coverage of the BBC website of the aggression against Gaza Strip in 2021, by comparing between its Arabic and English copies, moreover, to reveal the extent of the balance and bias in the news coverage in both languages, the comparison carried out in the Headline level, Multimedia level, Events Narration level, and Sources level. Critical discourse analysis CDA method used in order to uncover the ideological underpinnings of the two copies by shedding lights on the editorial policy trends towards both Palestinian and Isrealian. The Study targeted Six main media materials for analysis, published on the BBC website in both its Arabic and English news website, during the aggression period. The researchers took the sample’s representation of all periods of the aggression on Gaza into consideration. News was selected by searching the site's archive in its Arabic and English versions.